Exploring the link between relationship quality and loyalty: Gaining Insights into Manufacturer-Supplier Relationships - Lemke, Fred (Cranfield University, 2003)
Manufacturers across industry sectors are gradually reducing their supplier base. Consequently, suppliers need an appropriate strategy to ensure preferred supplier status. It is argued, that `softer' - or more intangible - relationship factors potentially have the power to distinguish suppliers. But what are the intangible factors? How does a customer value them? Do they have an impact on the supplier selection process at all? Questions like these describe an area that has become a topic of considerable debate. Surprisingly, the relationship quality idea, although recognised as an important concept, has hardly received any empirical attention. Therefore, the research question of the present PhD project is stated as follows: In commercial customer-supplier relationships, what is relationship quality (RQ) from the customer's standpoint and how does it relate to the customer's loyalty? The researcher explored the question in three German industry sectors: 1) Engineering, 2) Electronics, and 3) Process. Studies concerned with softer aspects of business-to-business relationships as well as research dealing with supplier selection processes are typically based on preconceived views. Condensing the understanding of relationship quality to a narrow and ambiguous definition, however, would simplify a complex issue. This thesis represents the first study that has explored in-depth the relationship quality concept and its influence on the customer's loyalty. The research comprised three stages. The first stage was a telephone survey of German managers involved in supplier management. The aim was to explore key issues of supplier management such as determining the way suppliers are selected and capturing views on supplier relationships. The second stage was concerned with the exploration of the quality of supplier relationships in detail and the case study approach was the chosen research strategy. The researcher conducted plant visits that included analysis of company documents and in-depth interviews. These were guided by the repertory grid technique. It was found that manufacturers rely on three tangible measures alone when selecting suppliers - price, product quality, and delivery performance. Furthermore, manufacturers have a clear view as to what high-quality supplier relationships are made of. The third stage determined the link between the quality of relationships and the manufacturer's loyalty. The researcher employed an experimental research strategy in the form of a conjoint analysis. Participants evaluated suppliers based on the three tangible and a selection of intangible relationship quality criteria. The study uncovered to what extent the softer relationship quality factors come (unconsciously) into play in the process of selecting long-term supplier relationships.